The Differential Effects of LMX and Regulatory Focus on Promotive and Prohibitive Voice - Chaoyu Wang; Jeeyoung Kim; Myung-Ho Chung (SAGE Open, 2023)
Employee voice plays a crucial role in driving constructive change within organizations. However, there is a lack of understanding regarding the distinct antecedents of different types of voice behaviors, namely promotive and prohibitive voice. This study aims to address this gap by examining the influence of interpersonal factors, such as leader-member exchange (LMX), and individual factors, specifically regulatory focus, on both types of voice behavior. By focusing on LMX and regulatory focus, we explore how these factors uniquely and interactively affect promotive and prohibitive voice. The study collected data from 167 Chinese employees in Guangdong province and Hong Kong. Our findings reveal a positive linear relationship between LMX and promotive voice, indicating that a strong leader-member relationship enhances employees’ willingness to contribute proactive ideas and suggestions. In contrast, we observed a curvilinear relationship between LMX and prohibitive voice, consistent with the “too-much-of-a-good-thing” effect. Furthermore, our study examines the unique effects of promotion and prevention focus on promotive and prohibitive voice, respectively. However, we did not find significant interaction effects between LMX and regulatory focus on voice behavior. These results suggest that the impact of LMX and regulatory focus on voice behavior operates independently rather than in combination. Theoretical implications of our findings contribute to the understanding of voice behavior, leadership, and regulatory focus literature.